Family Dispute Resolution by Litigation: Between Litigation and Mediation Efforts as a Reconciliative Solution - Sonjaya, Feny Ramadhani; Hanan, Rafie Muhammad Yasril; Sururie, Ramdani Wahyu (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
This study aims to determine the settlement of family disputes through litigation. The method used in this study is qualitative with the type of library research and uses an empirical normative-juridical approach, where the study focuses on the reciprocal correlation between law and the phenomena that occur. The results of the study indicate that the settlement of family disputes through litigation is a dispute resolution method in which there is a process of mutually disabling opposing evidence (op tegenspraak) and producing a win-lose solution. In fact, the resolution of household problems outside the court, such as mediation which in traditional societies is often carried out at the village level or tahkim which is carried out in large families through negotiation and arbitration. However, in the modern era, people now prefer to resolve family disputes through litigation in court so that married couples are forced to choose a court decision which mostly ends in divorce.